Use of the fluorescent dye tetramethylrhodamine methyl ester perchlorate for mitochondrial membrane potential assessment in human spermatozoa. (11th January 2017) - Uribe, P.; Villegas, J. V.; Boguen, R.; Treulen, F.; Sánchez, R.; Mallmann, P.; Isachenko, V.; Rahimi, G.; Isachenko, E.
Summary: Mitochondrial membrane potential (ΔΨm) is an indicator of sperm quality and its evaluation complements the standard semen analysis. The fluorescent dye JC‐1 has been widely used to assess sperm ΔΨm; however, some problems have been detected under certain experimental conditions. Another fluorescent compound, tetramethylrhodamine methyl ester perchlorate (TMRM), has been used in somatic cells and bovine spermatozoa but not in human spermatozoa. TMRM accumulates in hyperpolarised mitochondria and the fluorescence intensity of this compound correlates with ΔΨm. Thus, the aim of this study was to evaluate and validate the usefulness of the fluorescent dye TMRM for measuring sperm ΔΨm. The results showed that TMRM accurately detects sperm populations displaying either high or low ΔΨm. Moreover, TMRM was able to measure sperm ΔΨm under the experimental conditions in which JC‐1 had previously presented difficulties. Differences in ΔΨm according to sperm and semen quality were properly detected and a positive correlation between ΔΨm and conventional semen parameters was observed. Finally, a positive correlation was found between the ΔΨm measurement by TMRM and by the widely used JC‐1. In conclusion, TMRM is a simple, time‐effective method, easy to set in laboratories equipped with flow cytometry technology, and can accurately detect changes in ΔΨm with efficiency comparable to JC‐1 without its limitations.